2018
DOI: 10.1590/0102-672020180001e1359
|View full text |Cite
|
Sign up to set email alerts
|

Early Oral Feeding Post-Upper Gastrointestinal Tract Resection and Primary Anastomosis in Oncology

Abstract: Background: The practice of starving patients in the immediate period after upper gastrointestinal surgery is widespread. Early oral intake has been shown to be feasible and may result in faster recovery and decrease length of hospital. Aim:To evaluate the feasibility and safety of oral nutrition on postoperative early feeding after upper gastrointestinal surgeries. Methods: Observational cohort design study with convenience retrospective data in both genders, over 18 years, undergoing to total gastrectomy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 14 publications
0
20
1
13
Order By: Relevance
“…A 2015 randomized, controlled trial by Mahmoodzadeh et al[20] comparing early oral feeding on POD1 to delaying oral feeding after ROBF in patients undergoing transthoracic esophagectomy or total/partial gastrectomy also found that EOF alone was associated with shorter LOS, faster ROBF, and fewer readmissions. An observational cohort study from 2018 evaluating the timing of oral feeding after upper gastrointestinal surgery (including 24 esophagectomies) also found a significant decrease in LOS when patients were fed orally on POD1 vs POD3[21].…”
Section: Timing Of Feeding - Early Vs Delayedmentioning
confidence: 99%
“…A 2015 randomized, controlled trial by Mahmoodzadeh et al[20] comparing early oral feeding on POD1 to delaying oral feeding after ROBF in patients undergoing transthoracic esophagectomy or total/partial gastrectomy also found that EOF alone was associated with shorter LOS, faster ROBF, and fewer readmissions. An observational cohort study from 2018 evaluating the timing of oral feeding after upper gastrointestinal surgery (including 24 esophagectomies) also found a significant decrease in LOS when patients were fed orally on POD1 vs POD3[21].…”
Section: Timing Of Feeding - Early Vs Delayedmentioning
confidence: 99%
“…Moreover, Shoar et al[ 20 ] showed that for patients with upper gastrointestinal malignant tumors, EOF after surgery can lead to faster recovery and shorter postoperative hospitalization. Lopes et al[ 21 ] also indicated that early oral diet was safe and viable for patients undergoing upper gastrointestinal surgery. The studies of Laffitte et al[ 4 ] and Sierzega et al[ 5 ] showed that patients after radical gastrectomy could tolerate EOF, while there was no definite correlation between EOF and postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have evaluated the early oral feeding in the direct postoperative esophagectomy period, showing that the early oral feeding was not associated with an increased incidence of vomiting and nausea, nor was it considered a risk factor for anastomotic leakage. Moreover, those patients who received early oral feeding have a shortened hospital stay (25).…”
Section: Enteral Feeding Route-oral Nasoenteric Catheter and Jejunosmentioning
confidence: 99%